The effect of student-perceived teacher support on math anxiety: chain mediation of teacher–student relationship and math self-efficacy - Wang, Chao; Xu, Qing; Fei, Wei-qun (Frontiers in Psychology, 2024)
Abstract：This study investigates the mechanisms linking students' perceived teacher support with math anxiety, with a focus on the chain mediating roles of the teacher-student relationship and mathematics self-efficacy. Conducted with 401 fifth-grade students in China, the study utilized scales measuring the Students' Perceived Teacher Support, Teacher-Student Relationship, Math Self-Efficacy, and Math Anxiety. Results indicated that student-perceived math teacher support, teacher-student relationship, and math self-efficacy were all significantly negatively correlated with math anxiety. Notably, student-perceived math teacher support influenced math anxiety through the chain mediation of teacher-student relationship and math self-efficacy. Furthermore, the effect of students' perceived emotional support from math teachers on math anxiety, mediated by teacher-student relationship intimacy, was significant only among male students, not females. These findings underscore the importance of fostering positive teacher-student interactions and enhancing self-efficacy in reducing math anxiety among primary school students.